STANDAR PENILAIAN ASPEK PSIKOMOTORIK PENDIDIKAN AGAMA ISLAM - Hatta Fakhrurrozi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
Psychomotor assessment is characterized by the presence of physical activity and performance skills by students. Unlike the students 'cognitive assessment, psychomotor assessment is based on the actualization and implementation of students' understanding of the various subject matter that has been obtained in the classroom. In some of the subject matter, psychomotor assessment determines the success of a lesson. This article is a literature research. this article aims to find students' psychomotor assessment format in Islamic Religious Education subject matter. The results of this study conclude that the assessment of the success of learners is not only determined from the cognitive aspects, but also from the affective and psychomotor aspects. Standard psychomotor assessment is made different from the cognitive assessment, that is by way of describing the test scores. Psychomotor assessment should be held by direct observation of learners, can not only practiced by written tests.